A Systematic Review of Lymphangioleiomyomatosis on Diagnosis and Molecular Mechanism. (11th February 2021) - Dong, Xiaotong; Jin, Lvcheng; Wang, Ailan; Wu, Liping; Fan, Xintong; Hou, Qian; Li, Tianbao; Zhao, Ruilian; Zhang, Yunxiang
Abstract : Objective . Lymphangioleiomyomatosis (LAM) is a rare low-grade metastatic tumor; however, LAM patients were always found in young age with difficulty for diagnosis. Our study is aimed at observing the clinical characteristics of patients with lymphangiomatosis, including the clinical manifestations, imaging findings, histopathological features, and immunophenotype. Methods . We did a systematic review on LAM/PLAM cases, especially on male cases, and collected the clinical features and molecular mechanisms of PLAM based on previous findings. Results . Diagnosis criteria were summarized by combining CT scans, MRI, immunohistochemistry results, and gene sequencing results for effectively distinguishing between PLAM and similar diseases. Moreover, our study illustrated the molecular mechanism of PLAM as well as the signaling pathway involved in the disease initials. In addition, a male case was reported with differential diagnosis on the clinical manifestations, microscopic features, immunophenotypes, and genotypes. Conclusion . Our review will definitely improve the understanding of diagnosis and treatment in PLAM cases.